Estimation of Submerged Arc Plates Weldment Properties Using ANFIS and Regression Techniques - Hassan, Abdul Kareem F.; Jasim, Raad Jamal; Ashoor, Yousif Younis (Basrah Journal for Engineering Sciences, 2020)
The present work aims to build mathematical models based on experimental data to estimate the mechanical properties of submerged arc weldment. AISI 1020 low carbon steel plates 16mm thickness were welded according to orthogonal array in order to establish the relationship between input parameters (welding current, Arc voltage and welding speed) and output parameters (ultimate tensile stress, yield stress, impact energy and hardness) by submerged arc welding (SAW) process. The relationship between input and output parameters for the welding process are conducted using two suitable mathematical models the first one based on regression analysis, while the second one based on multi input single output ANFIS model for estimation of some mechanical properties of the welded plates. It was found that ANFIS results are closer to the experimental results than regression results. The optimal parameters (which give a maximum value of ultimate tensile strength (UTS), yield stress and impact energy; 446 MPa, 318 MPa and 213 J) are welding current is (380 Amp), Arc voltage is (25 V) and welding speed is (40 cm/min), while the maximum value of hardness number is (228 HV), when current welding is (380 Amp), Arc voltage is (25 V) and welding speed is (25 cm/min).